2021
DOI: 10.4269/ajtmh.20-1448
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Typhoid Fever Complicated by Ileal Perforation in an Urban Slum of Dhaka, Bangladesh

Abstract: Intestinal perforation is one of the most dangerous complications of typhoid fever and demands urgent hospitalization, diagnosis, and surgical management to reduce morbidity and prevent mortality. Here, we report a case of typhoidal intestinal perforation in a 19 year-old young man detected by passive surveillance during a cluster-randomized trial with Vi-tetanus toxoid conjugate vaccine (Typhoid Vaccine Acceleration Consortium: TyVAC) in an urban slum area in Mirpur, Dhaka, Bangladesh. The patient presented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…In contrast to the ndings of Khanam et al, (13) in Bangladesh, the median distance between the perforations and the ileocecal junction was 41.9 cm (range, 20-180 cm). This may be due to racial differences and the large sample size due to the high population density in rural settings.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…In contrast to the ndings of Khanam et al, (13) in Bangladesh, the median distance between the perforations and the ileocecal junction was 41.9 cm (range, 20-180 cm). This may be due to racial differences and the large sample size due to the high population density in rural settings.…”
Section: Discussioncontrasting
confidence: 83%
“…However, Shyamkumargupta et al in India observed that approximately 73% of respondents had perforations < 0.5 cm in size (3,9). In Bangladesh, Khanam et al, (13), in a similar report, the size of the perforations was variable, with a median diameter of 5.0 mm and a range of 1-25 mm.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Pakistan, India, and other tropical countries suffer from Typhoid fever, an endemic disease. 4,5 Even though surgery is considered a definite treatment, the choice of the exact surgical procedure remains controversial. Different authors have recommended numerous operative procedures in their studies, the most suggested being: i) simple primary repair of perforation; ii) repair of perforation with an intertransverse colostomy; iii) primary ileostomy; iv) single layer repair with an omental patch; v) resection and anastomosis.…”
Section: Introductionmentioning
confidence: 99%
“…They reported Rickettsia (37%) and dengue (9.6%) as the predominant causes of AFI in their study, along with very few cases of Coxiella, Leptospira, Bartonella, and chikungunya virus infections. Other than malaria in endemic zones, most single pathogen studies of acute febrile illness investigated enteric fever [21][22][23][24][25][26][27][28] and dengue [29][30][31][32][33][34][35][36][37] as these are common diseases in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%